Temporal variation of vaccination rates against bovine brucellosis in the Southeast of Goias State (Research, Society and Development, 2021)
The bovine brucellosis is an infectious disease, as well as a chronic disorder of compulsory notification, responsible for several losses and the institution of sanitary barriers. The study had the purpose of analyzing the tendency the long-term vaccination in the Southwestern micro-region of Goiás, in between the years 2015 and 2020. The rates of vaccination against bovine brucellosis were calculated, so, later, the time trends of the vaccination could be calculated and analyzed. The data about the vaccination of the cattle herd, during the relevant period were garnered from the Goiana Agency of Agricultural Defence (Agrodefesa). In the Southwest of Goiás, the vaccination rates against brucellosis was 59% on the first semester of 2015 and 35% on the second semester of the same year. In 2017, it was 54% in the first semester and 29% in the second. On the first semester of 2018, the rates observed was 48% and 25% on the second. On the first and second semesters of 2019, they were, respectively, 58% and 29%. Finally, on the first semester of 2020, it reached 58%. The average of the vaccination rates on the aforementioned semesters was 44%. The area with the least vaccination amongst those studied was Chapadão do Céu (8%), on the second semester of 2017, and variation rates between semesters were 15.13% (IC95% - 28.7 a 1). Santa Rita do Araguaia had the two highest vaccination rates, 117% - the highest, on the first semester of 2020 with variation rates between semesters of 8,57% (IC95% - 20,2 a 4,8) – and 92% - the second highest, on the first semester of 2017 and variation rates between semesters of 8,57% (IC95% - 20,2 a 4,8). The long-term time trends were stable on most of the assessed municipalities. Considering that most of the rates were lower than 70%, on all the relevant semesters, the stability is a negative development. The results suggest little evolution on the vaccination program against bovine brucellosis on the Goiano Southwest, which could affect the prevalence of the disease on the micro-region in a negative fashion.